2013
DOI: 10.1002/glia.22496
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline restrains glia and confers neuroprotection in a 6‐OHDA Parkinson model

Abstract: Neuron-glia interactions play a key role in maintaining and regulating the central nervous system. Glial cells are implicated in the function of dopamine neurons and regulate their survival and resistance to injury. Parkinson's disease is characterized by the loss of dopamine neurons in the substantia nigra pars compacta, decreased striatal dopamine levels and consequent onset of extrapyramidal motor dysfunction. Parkinson's disease is a common chronic, neurodegenerative disorder with no effective protective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 161 publications
6
74
0
6
Order By: Relevance
“…Co‐injection of intra‐nigral L‐AAA neutralized the LPS‐induced reactive GFAP + astrogliosis and exorbitant S100β production which correlated with a sizeable repression in dopaminergic neuronal loss and nigrostriatal dopamine depletion (Figure a–f). Our findings are similar to those of Lazzarini et al () who have shown that 6‐hydroxydopamine (6‐OHDA)‐induced motor dysfunction and dopaminergic neuropathology in the SNpc & striatum are associated with increases in GFAP + reactive astrocytes when assessed 25 days post unilateral striatal lesioning, whereas the neuroprotection conferred on foot of treatment with the antibiotic doxycycline is associated with a reduction in the nigral & striatal astroglial response to 6‐OHDA. L‐AAA relieves the nigrostriatal dopaminergic tract from the astroglial response to LPS, preventing the dopamine loss and facilitating improvements in motor function.…”
Section: Discussionsupporting
confidence: 91%
“…Co‐injection of intra‐nigral L‐AAA neutralized the LPS‐induced reactive GFAP + astrogliosis and exorbitant S100β production which correlated with a sizeable repression in dopaminergic neuronal loss and nigrostriatal dopamine depletion (Figure a–f). Our findings are similar to those of Lazzarini et al () who have shown that 6‐hydroxydopamine (6‐OHDA)‐induced motor dysfunction and dopaminergic neuropathology in the SNpc & striatum are associated with increases in GFAP + reactive astrocytes when assessed 25 days post unilateral striatal lesioning, whereas the neuroprotection conferred on foot of treatment with the antibiotic doxycycline is associated with a reduction in the nigral & striatal astroglial response to 6‐OHDA. L‐AAA relieves the nigrostriatal dopaminergic tract from the astroglial response to LPS, preventing the dopamine loss and facilitating improvements in motor function.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports have shown reductions in microglia using staining for Iba1 and Mac-1 antigens in the mouse brain after weeks of doxycycline administration implying that the use of this antibiotic could confound studies of brain inflammation (Lazzarini et al, 2013; Sultan et al, 2013). We have therefore considered the possibility that 7 days of 100 mg/kg doxycycline administration might affect the number and morphology of microglia and possibly TH immunoreactivity in the SNc.…”
Section: Discussionmentioning
confidence: 99%
“…In adult rats, we disrupted the sympathetic innervation of the PG by either performing a bilateral surgical removal of the SCG (SCGx), or by performing a decentralization procedure of the SCG (SCGd), which severed the connection between the ganglion and the sympathetic nerve trunk but left the SCG and its efferent nerves intact (Hartley et al, 2015;Savastano et al, 2010). We also challenged separate groups of adult rats pharmacologically, either via intraperitoneal (IP) administration of gramnegative bacteria wall components, lipopolysaccharides (LPS) (Ajmone-Cat et al, 2003;Cacci et al, 2008;Cunningham, Martinez-Cerdeño, & Noctor, 2013;Jiang-Shieh et al, 2005;Li et al, 2007;Xie et al, 2017), or by IP administration of the antibiotic doxycycline (DOX), which is an inhibitor of microglial function (Jantzie, Cheung, & Todd, 2005;Lazzarini et al, 2013;Santa-Cecilia et al, 2016;Sultan, Gebara, & Toni, 2013;Yrjanheikki, Keinanen, Pellikka, Hokfelt, & Koistinaho, 1998). The manipulations applied here stem from our current understanding about the tight interplay between microglia and neuronal activity, and between microglia and inflammatory elements induced by peripheral insults, such as bacterial infections (Catorce & Gevorkian, 2016;Colonna & Butovsky, 2017;Wake et al, 2013;Xie et al, 2017).…”
mentioning
confidence: 99%